Perbedaan Tingkat Minat Baca Siswa SMA Khadijah Surabaya Sebelum dan Sesudah Melaksanakan Program Penugasan Guru - Estiningtyas, Mawaddah Anindya; Hidayah, Imas Rahmadhtul (Program Studi Ilmu Perpustakaan dan Informasi, Universitas Islam Nusantara, 2021)
The issue of developing reading interest in students is an interesting study to discuss because the reading culture of Indonesian society has an effect on Indonesia's development. Creating the excitement of reading involves the role of all school communities. The assignment of teachers is expected to be a strategy to increase the intensity of visits and reading activities of students. This research uses quantitative decryptive research methods. The scope of this research is about the difference in the level of reading interest of high school students who follow the teacher assignment program with high school students who do not follow the teacher assignment program and the level of reading interest of high school students who follow the teacher assignment program. Data collection techniques carried out by researchers are the dissemination of questionnaires, observations, and literature studies. Data analysis techniques are carried out in a quantitative descriptive way as well as a comparative hypothesis test of two samples that have a correlation. The study used the significance formula in comparative testing between the values before the study and after the study with the T-test formula on a separate sample. Signification test results show that teacher assignment programs can increase reading interest in students.Keywords: interest in reading, school literacy movement, teacher's roleABSTRAKPersoalan menumbuhkembangkan minat baca pada siswa merupakan kajian menarik untuk dibahas. Mewujudkan kegemaran membaca melibatkan peran semua masyarakat sekolah. Adanya penugasan guru diharapkan menjadi strategi untuk meningkatkan intensitas kunjungan dan kegiatan membaca para siswa. Penelitian ini menggunakan metode penelitian dekriptif kuantitatif. Lingkup penelitian ini yaitu mengenai perbedaan tingkat minat baca siswa SMA yang megikuti program penugasan guru dengan siswa SMA yang tidak mengikuti program penugasan guru dan tingkat minat baca siswa SMA yang mengikuti program penugasan guru. Teknik pengumpulan data yang dilakukan oleh peneliti yaitu penyebaran kuesioner, observasi, serta studi pustaka. Teknik analisa data dilakukan dengan cara deskriptif kuantitatif serta uji hipotesis komperatif dua sampel yang memiliki korelasi. Penelitian ini menggunakan rumus signifikansi dalam pengujian perbandingan antara nilai sebelum penelitian dan sesudah penelitian dengan rumus T-test pada sampel terpisah. Hasil uji signifikasi menunjukkan bahwa program penugasan guru dapat meningkatkan minat baca pada siswa.